It Is Just a Matter of Time: Balancing Homologous Recombination and Non-homologous End Joining at the rDNA Locus During Meiosis - Sims, Jason; Rabanal, Fernando A.; Elgert, Christiane; von Haeseler, Arndt; Schlögelhofer, Peter (Frontiers in Plant Science, 2021)
Ribosomal RNA genes (rDNAs) are located in large domains of hundreds of rDNA units organized in a head-to-tail manner. The proper and stable inheritance of rDNA clusters is of paramount importance for survival. Yet, these highly repetitive elements pose a potential risk to the genome since they can undergo non-allelic exchanges. Here, we review the current knowledge of the organization of the rDNA clusters in Arabidopsis thaliana and their stability during meiosis. Recent findings suggest that during meiosis, all rDNA loci are embedded within the nucleolus favoring non-homologous end joining (NHEJ) as a repair mechanism, while DNA repair via homologous recombination (HR) appears to be a rare event. We propose a model where (1) frequent meiotic NHEJ events generate abundant single nucleotide polymorphisms and insertions/deletions within the rDNA, resulting in a heterogeneous population of rDNA units and (2) rare HR events dynamically change rDNA unit numbers, only to be observed in large populations over many generations. Based on the latest efforts to delineate the entire rDNA sequence in A. thaliana, we discuss evidence supporting this model. The results compiled so far draw a surprising picture of rDNA sequence heterogeneity between individual units. Furthermore, rDNA cluster sizes have been recognized as relatively stable when observing less than 10 generations, yet emerged as major determinant of genome size variation between different A. thaliana ecotypes. The sequencing efforts also revealed that transcripts from the diverse rDNA units yield heterogenous ribosome populations with potential functional implications. These findings strongly motivate further research to understand the mechanisms that maintain the metastable state of rDNA loci.